Carter-Karis collection - Wynne, Susan G. ([Microfilmed for Cooperative Africana Microform Project at Center for Research Libraries by] Univ. of Chicago, Joseph Regenstein Library, Dept. of Photoduplication, 1974)
Microfilm of documents deposited in the Melville J. Herskovits Africana collection of Northwestern University Library. The bulk of the material was issued by African, Indian, and Coloured political, cultural, and labor organizations. It includes the personal papers of A.W.G. Champion and Z.K. Matthews. A "small part" of these documents has been published as: From Protest to challenge: a documentary history of African politics, 1882-1964, edited by Thomas Karis (Stanford : Hoover Institution Press, 1972-1977)